Creating a Tourist Image for Poland for the European Union - Prylińska, Monika (Turyzm/Tourism, 2004)
The main aim of the article is to define the tourist image of Poland, stress its complexity and attempt to identify the stages which have led to the present image of foreign tourists. Three types of stereotypical image emerged during data analysis which led to the conclusion that due to a poorly selected tourist ‘offer', not answering the needs of EU tourist markets, not clearly identified with any tourist attraction, and with a negative, stereotypical image, Poland usually remains an unknown country. The article also presents the concept of 'tourist product selection' modelled on the demand of a given country and considers the promotion of those Polish attractions which could be of great interest to tourists, either as such attractions are not found in their own countries or because of a certain similarity enabling identification with them and comparison.